2012
DOI: 10.1007/s00586-012-2541-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of beta-tricalcium phosphate and bone marrow aspirate as a bone graft substitute in posterior lumbar interbody fusion

Abstract: Purpose Due to the disadvantages of iliac crest bone and the poor bone quality of autograft gained from decompression surgery, alternative filling materials for posterior lumbar interbody fusion cages have been developed. b-Tricalcium phosphate is widely used in cages. However, data regarding the fusion rate of b-TCP assessed by computer tomography are currently not available. Materials A prospective clinical trial involving 34 patients (56.7 years) was performed: 26 patients were treated with single-level, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
1
19
1
2
Order By: Relevance
“…Solid fusion was achieved in 77.8 % of the patients, which is lower than the 83.9 % observed in our study [24]. Okuda et al also reported on L4-S1 (%) 2 (6.4 %) [26,27]. More recently, Johnson et al published a randomized control trial comparing concentrated BMA mixed with allograft to ICBG in lumbar fusions.…”
Section: Discussioncontrasting
confidence: 78%
“…Solid fusion was achieved in 77.8 % of the patients, which is lower than the 83.9 % observed in our study [24]. Okuda et al also reported on L4-S1 (%) 2 (6.4 %) [26,27]. More recently, Johnson et al published a randomized control trial comparing concentrated BMA mixed with allograft to ICBG in lumbar fusions.…”
Section: Discussioncontrasting
confidence: 78%
“…The improvements in clinical outcomes reported here with the lateral approach are similar to traditional open approaches to the lumbar spine for the treatment of symptomatic lumbar stenosis, including posterior, anterior, and transforaminal interbody fusion. Thaler et al [25] reported significant improvements in ODI and VAS scores for leg and back pain at a minimum of 1-year followup after posterior lumbar interbody fusion using beta-tricalcium phosphate and bone marrow aspirate bone graft substitute. Additionally, Slosar et al [24] have reported significant improvements in ODI after transforaminal lumbar interbody fusion procedures with allograft bone and BMP-2 (INFU-SE TM ).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the achieved arthrodesis rates in MI-TLIFs between the cohorts of local AB and silicate hydroxyapatite ceramic bone graft expander (Actifuse TM ) or local AB and rh-BMP-2, a radiographical arthrodesis of 65% in the Actifuse cohort and 92% in the rh-BMP-2 cohort were achieved 25) . Only in 26.7% of the levels solid fusion, in 34.1% indeterminate and in 38.6% inadequate fusion were assessed in PLIFs filled with β-tricalcium phosphate (β-TCP) and bone marrow aspirate (BMA) based on CT at 12 months postoperative 32) . In another study, using β-TCP with a resorbable polymer (ChronOS TM Strip) together with BMA and local AB in posterolateral fusion together with interbody support, interbody fusions of 54.1% and 71.2% were achieved in CTs at, respectively, 12 and 24 months postoperative 15) .…”
Section: Discussionmentioning
confidence: 99%